Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species - Perry, Ryan K.; Heraty, John M. (Zootaxa, 2021)
The genus Zagrammosoma Ashmead (Hymenoptera: Eulophidae) is revised. Twenty-six species are recognized, of which 23 have been molecularly verified in a phylogenetic context using 28S, ITS2, and COI. Zagrammosoma is recovered as monophyletic, worldwide in distribution, and morphologically distinct from Cirrospilus Westwood. Zagrammosoma interlineatum Girault stat. rev. is elevated from synonymy. The following synonymies are proposed: Zagrammosoma mirum Girault under Zagrammosoma flavolineatum Crawford n. syn., Zagrammosoma dulanense Cao & Zhu under Zagrammosoma talitzkii Bouček n. syn. The following species are described as new: Zagrammosoma calvini Perry n. sp. (Argentina, Chile), Zagrammosoma deliae Perry n. sp. (Peru), Zagrammosoma fisheri Perry n. sp. (USA), Zagrammosoma galapagoense Perry n. sp. (Ecuador: Galapagos Islands), Zagrammosoma headricki Perry n. sp. (Mexico, USA), Zagrammosoma metallicum Perry n. sp. (USA), Zagrammosoma occidentale Perry n. sp. (Mexico, USA), Zagrammosoma triangulum Perry n. sp. (USA), Zagrammosoma trifurcatum Perry n. sp. (Belize, USA), Zagrammosoma villosum Perry n. sp. (Nearctic, Neotropical), Zagrammosoma yanegai Perry n. sp. (Thailand). The following new combination is proposed: Cirrospilus variegatus (Masi) n. comb, from Zagrammosoma. Descriptions, distribution maps, host associations, and a key to all known species are provided.